State Land Management for Orderly Administration of Land in Regencies/Cities - Rizqi Abdulharis; Ida Nurlinda; Ari Zakaria; Alfita Puspa Handayani (Pusat Penelitian dan Pengabdian kepada Masyarakat, Sekolah Tinggi Pertanahan Nasional, 2022)
The concept of state control over land is the underlying concept of land management in Indonesia, which is physically represented by the state land. The control of the utilization of state land is one of the sub-activities of the regency/city government. However, there has been no study on these sub-activities carried out based on the Regulation of the Minister of Home Affairs Number 90 of 2019, Law on Job Creation and its derivatives, and the concept of land administration. This paper presents the results of the study on state land management in regencies/cities. This study was conducted using content several methods: content analysis, secondary data analysis, and classification analysis based on the concept of land administration. The data collected and analyzed were laws and regulations on land and their implementation in the context of land administration in several areas in Indonesia. The results of this study indicate that there are fundamental changes in the definition of state land, where the Law on Job Creation and its derivatives do not define land that has been attached to land rights as state land. In addition, the Regulation of the Minister of Home Affairs Number 90 of 2019 and the Law on Job Creation and its derivatives have regulated the authority of the regency/city government in the administration of the control, use, development, and assessment of state land. By considering the definitions and laws and regulations regarding state land, state land management can be implemented through (1) the development of the state land cadaster system, (2) coordination with the agencies administering the control of state land, and (3) the regulation and implementation of the use, development, and assessment of state land. Keywords: land administration, regency/city, state land